A first-order simulation based on contextually aware sensor network home in minimizing energy usage by occupancy while maintaining thermal comfort - Bin F.C.; See O.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Houses; Sensor networks; Thermal comfort; Eco-friendly; Experimental system; First order; Minimizing energy; Energy utilization